Tubulin Folding Cofactor D Deficiency: Missing the Diagnosis With Whole Exome Sequencing. (July 2021) - Quitmann, Christina M.; Rust, Stephan; Reunert, Janine; Biskup, Saskia; Fiedler, Barbara; Marquardt, Thorsten
Two siblings with an early onset of a neurodegenerative disease were presented with muscular hypotonia, secondary microcephaly, and severe developmental delay. Seizures were refractory to treatment but could be controlled with a ketogenic diet. Over the course of 5 years, whole exome sequencing (WES) was performed twice in both children. The first time the diagnosis was missed. The next one revealed compound heterozygous mutations in the gene coding for the tubulin folding cofactor D. Technical improvements in WES mandated a new investigation after a few years in children where the diagnosis has not been found.